The Effectiveness of Engklek baca in Improving the Early Reading Ability of Children with Reading Difficulties - Damayanto, Angga; Hayati, Nurfallah; Cantika, Listya Mutiara (Universitas Negeri Malang, 2024)
This research aims to prove that engklek baca as a learning media based on local wisdom can be an alternative learning media that can improve initial reading skills in students with reading barriers at Bumiaji 3 Sragen State Elementary School. This research uses an experimental method using a single subject design or Single Subject Research (SSR). Data collection was carried out using a one group pre-test - post-test design consisting of one predetermined group. In this design, the test is done twice, namely a pre-test and a post-test done after the students are given treatment. The data that has been obtained shows that engklek reading as a learning medium has proven to be effective in improving the reading skills of students with reading barriers. From the average value obtained, there is an increase in the average and there is a difference between the two data, namely 20. The hypothesis can be accepted because there is a difference between after the treatment given and before the treatment was given to students. The difference in question is an increase in the reading ability of students with reading barriers.